2005
DOI: 10.1103/physrevb.72.144526
|View full text |Cite
|
Sign up to set email alerts
|

Vortex radiation in long narrow Josephson junctions: Theory and experiment

Abstract: We study theoretically and experimentally the dynamics of vortices in long, extremely narrow Josephson junctions. Using a variational approach, the current-voltage characteristics are calculated for junctions of different widths. The analytically and numerically calculated current-voltage characteristics show good agreement. We find that the decrease of the junction width leads to a substantial increase of the maximum velocity of vortices. Due to the interaction with stray magnetic fields outside the junction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…[1][2][3][4][5] Development of the nonlocal electrodynamics of these junctions is still in progress and is a subject of growing theoretical and experimental interest. [6][7][8][9] In particular, it was shown that the nonlocality caused by the stray fields slows down the electromagnetic waves propagating along the junction. 3 This effect leads to an interesting and important result-Cherenkov radiation by fast moving Josephson vortices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Development of the nonlocal electrodynamics of these junctions is still in progress and is a subject of growing theoretical and experimental interest. [6][7][8][9] In particular, it was shown that the nonlocality caused by the stray fields slows down the electromagnetic waves propagating along the junction. 3 This effect leads to an interesting and important result-Cherenkov radiation by fast moving Josephson vortices.…”
mentioning
confidence: 99%
“…3 This effect leads to an interesting and important result-Cherenkov radiation by fast moving Josephson vortices. 3,9 The features of the edge-type junctions such as large I c R products and low noise are attractive for applications. 10 Nonlocality caused by the long-range stray fields is especially important for physics of series of interchanging 0-and -shifted junctions.…”
mentioning
confidence: 99%
“…1(b)]. Here we recall that several systems governed by the SG equation show evidence of soliton motion, including not only JJs [70][71][72][73][74][75][76] but also the relativistic field theory, mechanical transmission lines, and atomic, particle, and condensed matter physics. A peculiar dynamics is also present in the superconducting device analyzed in this work.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the drop of the orderparameter phase across the superconducting banks is defined by an integral equation. [1][2][3][4][5][6][7][8] The kernel of this equation depends on the tunneling characteristics and on the spatial distribution of the stray fields at the film surfaces. In other words, electrodynamics in edge-type thin-film Josephson junctions is nonlocal.…”
Section: Introductionmentioning
confidence: 99%